Coming of Age in Byzantium Adolescence and Society - Ariantzi, Despoina (Millennium - Studien/Millennium Studies, 2017)
The Millennium Studies seek to cross borders, boundaries between epochs and regional spaces, as well as boundaries between disciplines. Millennium is international, transdisciplinary and epoch-wide. The editorial board and the advisory board represent a broad spectrum of subjects: articles in art and literary criticism are just as right as historical, theological and philosophical contributions to the Latin and Greek cultures as well as to the oriental ones.